Pemanfaatan Citra Satelit untuk Mendeteksi Zona Potensi Penangkapan Ikan Cakalang - Sagitama, Daniel Angga; Marsisno, Waris (Politeknik Statistika STIS, 2024)
North Sumatra has some of the main commodities of fishing, one of which is skipjack tuna. During the period from 2019 to 2021, the production of skipjack tuna in North Sumatra has declined. To help fishermen find out where the fish are gathering, it is necessary to map Potential Fishing Zone (PFZ) using remote sensing methods. The research is aimed at implementing remote sensing methods for PFZ detection using Aqua-MODIS sensor data, determining sea surface temperature spread (SST) and chlorophyll-a concentration, as well as forming a monthly PFZs map. Furthermore, the highest SST occurred in February at 34.5°C and the lowest in December at 27.3°C. Meanwhile, high concentrations of chlorophyll-a tend to accumulate near the coast. As a result of the estimate of the potential zone for catch, September has the most potential points followed by October, while the months with the least potential points are January, July, and March. From the results, it can be said that the best time to catch skipjack tuna in the West Indian Ocean, the Nias Islands and the Sibolga Nias waters is predicted to be in September and October.